2017
DOI: 10.32771/inajog.v4i4.444
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Preeclampsia with Severe Features

Abstract: Objective: To describe the characteristics of preeclampsia with severe features and their risk factors. Method: This study was a retrospective medical record review of demographic characteristics, obstetric and medical data of preeclampsia with severe features in Dr. Cipto Mangunkusumo Hospital from July to December 2014. Result: There were 1,013 deliveries which 183 patients of them were diagnosed as preeclampsia with severe features (18.06%). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Another study showed that term pregnancy had a higher risk of severe preeclampsia-eclampsia compared with preterm pregnancy. However, the severity of complications in preeclampsia had an association with preterm delivery 13,14 . This result is reciprocal with the theory of placental implant ischemia, which states that preeclampsia increases with increasing gestational age.…”
Section: Pattern Of Antihypertensive Medication Usementioning
confidence: 99%
“…Another study showed that term pregnancy had a higher risk of severe preeclampsia-eclampsia compared with preterm pregnancy. However, the severity of complications in preeclampsia had an association with preterm delivery 13,14 . This result is reciprocal with the theory of placental implant ischemia, which states that preeclampsia increases with increasing gestational age.…”
Section: Pattern Of Antihypertensive Medication Usementioning
confidence: 99%